(untitled) (Geography and Tourism, 2018)
Source literature emphasizes the importance of lakes in the development of tourism-related functions of a given area. These functions are both connected with the lake itself, and with adjacent areas, based on the proximity of the water (Smith, 2003; Choiński and Borkowski, 2008; Duda-Gromada and Potocka, 2010). From the perspective of recreation, access to the lake is an important factor determining the presence of people on its shore. Accessibility of the shore should be understood as free access, with the option to rest, engage in recreation and bathe. This article presents a proposal for a natural and anthropogenic classification of lakeshores. It was employed in assessing the resources and recreational use of Lake Głębokie near Szczecin. The features and parameters of the lakeshore were assessed on the basis of a field survey and the applied valorization procedure. The analysis presented here was based on studies conducted in 2012 and 2017.